Building Family Resilience For Employees of the Pekanbaru Diniyah Foundation Islamic Law Perspective - Nurliana, Nurliana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The research is motivated by various family problems of married people, some family conditions are weak so that they are easily shaken and end in divorce. There are some families who look strong with all the problems so that the family survives, not shaken by any situation and condition. In this case the researcher is interested in conducting a research on how to build family resilience for the employees of the Diniyah Pekanbaru Foundation from the Perspective of Islamic Law. An urgent research, to find out the basic principles of family resilience, aims to educate people in fostering and maintaining families, not easily shaken by the problems that occur. The research method used is descriptive qualitative research using the triangulation method through data display, data presentation, drawing conclusions, analyzed through content analysis. The research sample is 195 respondents. Research findings; need to understand the purpose of marriage to build a samara family the answer of the respondent is 15%. Understanding each other's roles by applying the principle of mutual help Respondents answer 52%. Implementing Islamic values ​​in the family is 18%. Fulfilling the needs of nutrition, education, health and future investment of 15%. From the perspective of Islamic law, employees of the Diniyah Pekanbaru Foundation in general choose to carry out psychological aspects of family resilience by implementing human values, the principle of taawun and Islamic values ​​in the family so that physical needs accompany them.